Mercury Elemental Storage Tank Design - Restiawaty, Elvi; Bindar, Yazid; Aslan, Christian; Masduqi, Alif Lutfia (Dept. of Chemical Engineering, Diponegoro University, 2020)
Mercury is a liquid metal that has properties such as toxic, persistent, bioaccumulating, and its vapor can spread around sources so that it is harmful to humans. Despite having dangerous properties, mercury is found in some goods, products, and also waste. Mercury is indicated to be used in several industries, such as artisanal and small-scale gold mining and coal-fired steam power plants. Based on health and environmental considerations, mercury must ultimately be removed from the eco cycle. Mercury storage systems in the long term must be solved so that sustainable development for future generations can be achieved. Currently, there is still no mercury storage system in Indonesia with a good standard design, so the conceptual design study of the mercury elemental storage system is important. In this paper, the storage tanks with a mercury capacity of 35 kilograms, one tonne, and two tonnes were designed to meet mercury storage standards. Several design criteria were used as model development, such as storage capacity, height level, safety factor material, storage temperature, tank life span, and symbols and label. The design results presented in this paper are dimension and engineering drawing of the storage tanks and attributes like spill tray, pallet, and rack.Keywords: environment; hazardous and toxic material; Indonesia; mercury; storage tanks